Variability in Glycemic Control with Temperature Transitions during Therapeutic Hypothermia - Krystal K. Haase; Jennifer L. Grelle; Faisal A. Khasawneh; Chiamaka Ike (Critical Care Research and Practice)
Purpose. Patients treated with therapeutic hypothermia (TH) and continuous insulin may be at increased risk of hyperglycemia or hypoglycemia, particularly during temperature transitions. This study aimed to evaluate frequency of glucose excursions during each phase of TH and to characterize glycemic control patterns in relation to survival. Methods. Patients admitted to a tertiary care hospital for circulatory arrest and treated with both therapeutic hypothermia and protocol-based continuous insulin between January 2010 and June 2013 were included. Glucose measures, insulin, and temperatures were collected through 24 hours after rewarming. Results. 24 of 26 patients experienced glycemic excursions. Hyperglycemic excursions were more frequent during initiation versus remaining phases (36.3%, 4.3%, 2.5%, and 4.0%, p=0.002). Hypoglycemia occurred most often during rewarming (0%, 7.7%, 23.1%, and 3.8%, p=0.02). Patients who experienced hypoglycemia had higher insulin doses prior to rewarming (16.2 versus 2.1 units/hr, p=0.03). Glucose variation was highest during hypothermia and trended higher in nonsurvivors compared to survivors (13.38 versus 9.16, p=0.09). Frequency of excursions was also higher in nonsurvivors (32.3% versus 19.8%, p=0.045). Conclusions. Glycemic excursions are common and occur more often in nonsurvivors. Excursions differ by phase but risk of hypoglycemia is increased during rewarming.